2020
DOI: 10.1111/plb.13153
|View full text |Cite
|
Sign up to set email alerts
|

Response of nutrient resorption of Leymus chinensis to nitrogen and phosphorus addition in a meadow steppe of northeast China

Abstract: Nutrient resorption, one of the most important strategies for plant nutrient conservation, is significantly affected by soil fertility. However, the effects of experimentally altered soil fertility on plant N and P resorption are poorly understood. The potential nutrient resorption response mechanisms of the dominant species Leymus chinensis to six N addition levels (0, 2.5, 5, 10, 20 and 40 g·N·m−2·year−1), two P addition levels (0 and 10 g P·m−2·year−1) and their interactions were studied after 3 years of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The leaf area and N concentrations varied between the different N treatments, with a significant increase in the leaf N concentrations under higher N rates. However, the N addition rates had no, or even negative effects, on the specific leaf area, aligning with previous field research and recent meta-analyses (Lü et al, 2016;Zhang et al, 2018;Shi et al, 2020). Our results revealed that the leaf area, LNC mass , and N absorption between shrub patches were stimulated by N, whereas N had no effect on the specific leaf areas and LNC area between the shrubs.…”
Section: Discussionsupporting
confidence: 90%
“…The leaf area and N concentrations varied between the different N treatments, with a significant increase in the leaf N concentrations under higher N rates. However, the N addition rates had no, or even negative effects, on the specific leaf area, aligning with previous field research and recent meta-analyses (Lü et al, 2016;Zhang et al, 2018;Shi et al, 2020). Our results revealed that the leaf area, LNC mass , and N absorption between shrub patches were stimulated by N, whereas N had no effect on the specific leaf areas and LNC area between the shrubs.…”
Section: Discussionsupporting
confidence: 90%
“…N addition led to an increase in the LN of the two species ( Figure 1 ), which corroborates the results of previous studies ( Huang et al, 2012 ; Lü et al, 2013 ). Nitrogen addition caused an increase in soil inorganic N concentrations, which subsequently enhanced the N concentrations in the leaves ( Shi et al, 2020 ). Moreover, N addition increased the re-absorption rate of plant N ( Lü et al, 2012 ; Cao et al, 2021 ), which in turn increased the plant N content.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a subtropical forest, the leaf [N] did not respond to N addition, but [P] increased, resulting in a decrease in the N:P of leaves [22]. In grassland, although N addition reduced the N resorption efficiency (NRE), it significantly promoted an increase in leaf [N], [P], and N:P [23]. A similar response was found in N and P allocation patterns in leaves in a wetland [24].…”
Section: Introductionmentioning
confidence: 99%